f(x) = 5-x, g(x) = -9x+7 Find (f + g)(x).
f(x) = 5-x, g(x) = -9x+7 Find (f + g)(x).
f(-5) for f(x) = {7x if x ≤ -1 {x-9 ...
The graph of y = -5(x-4)^2+7 can be obtained from the graph of y = x^2 by shifting horizontally__ units to the____, vertically stretching by a factor of___, reflecting across the__-axis, and shifting...
The graph of y = -10|x| can be obtained from the graph of y = |x| by vertically stretching by a factor of___ and reflecting across the__-axis.
The graph of y = x^2 is shifted 4 units to the right. This graph is then vertically stretched by a factor of 5 and reflected across the x-axis. Finally, the graph is shifted 8 units upward.